2019
DOI: 10.1111/cid.12816
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of in vivo assessed retention forces in one‐piece mini dental implant‐retained mandibular overdentures: 5‐Year follow‐up of a prospective clinical trial

Abstract: Background The evolution of retention forces in one‐piece mini dental implants (MDIs) retaining implant overdentures (IODs) is of major importance, as the male parts cannot be exchanged, due to the implant design. Purpose To report the evolution of retention forces of one‐piece MDIs, retaining mandibular IODs with ball/ O‐ring attachments during 5 years assessed in vivo. Materials and Methods Four MDIs were installed in the interforaminal region and immediately loaded using the existing mandibular complete den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…We also observed no influence of implant position on ΔMBL values. Another publication on the same study cohort, focusing on retentive forces of the IODs at the male and female parts, showed a significant loss of the mean retention force at the male part only at implant site 34 (Abou‐Ayash et al, 2019). Interestingly, the highest mean ΔMBL was found at the same implant site, which confirms the theory that the forces at this site might have been different relative to the other implant sites.…”
Section: Discussionmentioning
confidence: 97%
“…We also observed no influence of implant position on ΔMBL values. Another publication on the same study cohort, focusing on retentive forces of the IODs at the male and female parts, showed a significant loss of the mean retention force at the male part only at implant site 34 (Abou‐Ayash et al, 2019). Interestingly, the highest mean ΔMBL was found at the same implant site, which confirms the theory that the forces at this site might have been different relative to the other implant sites.…”
Section: Discussionmentioning
confidence: 97%
“…1-10 Among the possible treatment choices, the implant-retained mandibular overdenture (IOD) can differ depending on the design, position, and implant number and according to the patients' clinical presentation. 2,[11][12][13][14] Despite the benefits of IODs, patients might decline the treatment because of cost, fear of oral surgery, or psychological issues. 15,16 Moreover, standard-diameter implants might not always be clinically possible for anatomic or financial reasons.…”
mentioning
confidence: 99%
“…1b), as described in a previous study. 17 The disconnections were not performed at a predefined speed.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] Under in-vivo conditions, it has been shown that the initial retention forces in one-piece MDI retained overdentures can be reestablished, just by exchanging the O-rings, even after a 5-year period, which proves the theory of the male parts' and matrices' low wear in this kind of system. 17 But due to the pronounced deformation of O-rings during the connection and disconnection from patrices, the reproducibility of the retention forces, even of pristine O-rings has been questioned. 14 Furthermore, the influence of the matrix-and the O-ring diameter on the retention forces and its' reproducibility has not been scientifically evaluated.…”
Section: Introductionmentioning
confidence: 99%